2001
DOI: 10.1097/00004647-200101000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Ischemic Brain EDEMA and Cerebrovascular Injury after Ischemic Preconditioning in the Rat

Abstract: Summary: Ischemic preconditioning (IPC) induces neuroprotection to subsequent severe ischemia, but its effect on the cerebrovasculature has not been studied extensively. This study evaluated the effects of IPC on brain edema formation and endothelial cell damage that follows subsequent permanent focal cerebral ischemia in the rat. Transient (15 minute) middle cerebral artery occlusion (MCAO) was used for IPC. Three days after IPC or a sham operation, permanent MCAO was induced. Twenty-four hours after permanen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 42 publications
10
73
0
1
Order By: Relevance
“…Atropine and vagotomy blocked this promotion caused by intravenous injection of ghrelin. Masada et al (2001) reported that ghrelin regulates gastric kinetics via neuropeptide-Y1 receptor and nonselective corticotropin releasing factor receptor-1 in the paraventricular nucleus (Tebbe et al, 2005). Ghrelin is regulated by nutritional and hormonal factors.…”
Section: Serum Ghrelin and Small Intestinal Motilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Atropine and vagotomy blocked this promotion caused by intravenous injection of ghrelin. Masada et al (2001) reported that ghrelin regulates gastric kinetics via neuropeptide-Y1 receptor and nonselective corticotropin releasing factor receptor-1 in the paraventricular nucleus (Tebbe et al, 2005). Ghrelin is regulated by nutritional and hormonal factors.…”
Section: Serum Ghrelin and Small Intestinal Motilitymentioning
confidence: 99%
“…The concomitant effect causes decrease in enteric motility, and the increase of serum ghrelin is compensatory. Previous studies showed that once the middle cerebral artery was blocked for 15 min, heat shock protein 70 (HSP70) can be greatly synthesized to prevent ischemic brain edema and cerebrovascular damage in rats (Masada et al, 2001). We proposed that increased ghrelin may be released from the gut or the central nerve system such as thalamencephalon, pituitary, and hippocampus.…”
Section: Serum Ghrelin and Small Intestinal Motilitymentioning
confidence: 99%
“…Brains were rapidly removed and the cortex ipsi-and contralateral to the MCA occlusion was sampled as described previously (Masada et al, 2001). In brief, the hemisphere was divided, and the brain stem, hippocampus, cerebellum, and thalamus were removed.…”
Section: Blood-brain Barrier Disruptionmentioning
confidence: 99%
“…HSP-70 also increases the levels of anti-apoptotic proteins, Bcl-2 and Bcl-xL, thus serving as another mechanism to increase the anti:pro apoptotic ratio and push neurons toward cellular survival, especially in the setting of ischemia/reperfusion (Liebelt et al, 2010;Ohtsuka and Suzuki, 2000). Multiple studies have shown that ischemic preconditioning induces HSP-70 expression and promotes neuroprotection (Chen and Simon, 1997;Kirino et al, 1991;Masada et al, 2001). Despite these benefits, the effects of HSP-70 are limited.…”
Section: Heat Shock Proteinsmentioning
confidence: 99%